Intervención de enfermería en un paciente geriátrico pluripatológico con insuficiencia renal - Samaniego Mendoza, Evelyn Anabel (2024)
The present case study focused on nursing intervention in a multipathological geriatric patient with renal failure, a population that presents unique clinical challenges due to the interaction of multiple pathologies and the frailty associated with advanced age. Comprehensive and personalized nursing care was essential to improve the quality of life and clinical management of this patient. Thorough evaluation of the patient's medical history and comorbidities allowed for an individualized care plan. Effective nursing intervention begins with a detailed analysis of the medical history, current medications, emotional state, and the evaluation includes management of specific symptoms associated with kidney failure, such as fatigue, edema, and alterations in fluid and blood balance. electrolytes, we nurse must strictly monitor water balance, promote an adequate diet and restrict sodium and potassium intake according to medical indications. Safe medication management, interdisciplinary coordination, and patient and family education played a crucial role in optimizing drug therapy, improving treatment adherence, and promoting self-care. Additionally, care is essential to ensure that all of the patient's needs are met. Nurses must work closely with other health professionals, including physicians, nutritionists and social workers, to develop and perform better work. Finally, the study highlighted the importance of continuous evaluation, modification of the care plan is essential to adapt to changes in the patient's condition. Constant communication with the health team and the patient's family ensures coordinated and patient-centered care, thus improving health outcomes and quality of life for multipathological geriatric patients with kidney failure.